2016
DOI: 10.1111/1750-3841.13327
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and Characterization of Compounds with Antioxidant Activity in Lycium barbarum Using High‐Performance Thin Layer Chromatography Coupled with DPPH Bioautography and Tandem Mass Spectrometry

Abstract: Methanol extracts from 50 batches of Lycium barbarum (L. barbarum, wolfberry) in China were compared and characterized using high-performance thin-layer chromatography coupled with 2,2-diphenyl-1-picrylhydrazyl (DPPH) bioautography (HPTLC-DPPH) and electrospray ionization quadrupole time-of-flight tandem mass spectrometry (ESI-Q-TOF-MS/MS), respectively. Results showed that similar components occupying the major antioxidant activity existed in L. barbarum collected from different origins. However, the average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
(35 reference statements)
0
11
0
Order By: Relevance
“…In bow milk, know to have very low antioxidant properties and so used as negative control [ 18 ], TCP value was 17 ± 1 mgGAE/100gr and ORAC value was 855 ± 2 μmolTE/100gr DW. In LB berry extratcs, know to have very high antioxidant properties and so used as positive control [ 19 ], TCP value was 943 ± 231 mgGAE/100gr and ORAC value was 26502 ± 3807 μmolTE/100gr DW (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In bow milk, know to have very low antioxidant properties and so used as negative control [ 18 ], TCP value was 17 ± 1 mgGAE/100gr and ORAC value was 855 ± 2 μmolTE/100gr DW. In LB berry extratcs, know to have very high antioxidant properties and so used as positive control [ 19 ], TCP value was 943 ± 231 mgGAE/100gr and ORAC value was 26502 ± 3807 μmolTE/100gr DW (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The detection wavelength for densitometry scanning was chosen based on the overlaid absorption spectra of antioxidant bands. The overlaid spectra revealed that the maximum absorption wavelength for antioxidant bands was 535 nm, and 535 nm was selected for detection (Lam and others ).…”
Section: Resultsmentioning
confidence: 99%
“…HPTLC not only greatly reduces analysis time and consumption of organic solvents, but also provides adequate resolutions for the isolation of compounds with antioxidant activity because of the smaller particle size of stationary phase compared to general TLC plate (Tistaert and others ). Antioxidants isolated by HPTLC after postderivatization of DPPH solutions were displayed in the form of yellowish fluorescent bands with purple background, which were easy to be identified and were of high sensitivity (Jesionek and others ; Lam and others ). Overall, HPTLC‐DPPH bioautography can serve as an efficient approach to isolate compounds with antioxidant activity and to identify multiple samples in parallel.…”
Section: Introductionmentioning
confidence: 99%
“…Goji berries are characterized red-orange colour formed by carotenoids [23]. One of the most important components of goji berries are polyphenols with high antioxidant activity [24]. The biggest group of components are compexed polysaccharides, and moreover vitamins as ascorbic acid, tiamin, ryboflavin or glucopyranosids.…”
Section: Introductionmentioning
confidence: 99%